UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BUASBUAS (Premna cordifolia Linn.) TERHADAP GAMBARAN HISTOPATOLOGI PARU TIKUS (Rattus norvegicus) WISTAR JANTAN PASCA PAPARAN ASAP ROKOK - ., Kristina Lusty Tohomi (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Cigarette smoke is one of free radical source that can cause oxidative stress, emphysema, and inflamation on lung. Leaves of Premna cordifolia Linn. isone of antioxidant that can neutralize the free radical in body. The purpose of theresearch is to find the antioxidant activity of Premna cordifolia leaves in reducinglung’s damage and to find the effective dose that can reduce lung’s damage afterexposure of cigarette smoke. Dried leaves of Premna cordifolia are maseratedwith ethanol 70%. Rats are divided into five groups, Group without treatment(CMC control), group that exposed to smoke, three groups that treated with 200(P1), 400 (P2), and 600mg/kgBW (P3) of ethanolic extract of Premna cordifolialeaves after smoke exposure, and one group that treated with 18mg/kgBW ofvitamin E as positive control after smoke exposure. All groups were treated withthree cigarette without filter for 14 days. All rat were terminated on the fifteentday. Right lung were collected and subjected to necropsy and stained withHematoksilin-Eosin. The result show that all doses of ethanolic extract of Premnacordifolia reduce lung damage in enlarge alveolar, thickening of alveolar’s wall,and infiltration of inflmation cells in rats. The effective dose is 600mg/kgbwbecause the potential of Premna cordifolia leaves extract was same with thepotential of positive contol in reducing the lung damage. Keywords : Antioxidant, Premna cordifolia, Lung histopathology, Cigarettesmoke